Incidentally detected asymptomatic hepatitis C virus infection with significant fibrosis: Possible impacts on management - Rakesh Kumar Gupta; Puja Sakhuja; Kaushik Majumdar; Shahajad Ali; Siddharth Srivastava; Sanjeev Sachdeva; Barjesh C Sharma; Amarender S Puri (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: Liver biopsy may be considered in patients with hepatitis C virus (HCV) infection to assess the severity of liver injury and stage of fibrosis, thereby guiding therapeutic decisions. In addition, advanced stage also necessitates surveillance for hepatocellular carcinoma. The aim of this study was to assess whether transaminase (alanine transaminase [ALT]) levels and RNA titers correlate with the histological activity index (HAI) and fibrosis (F) stage in asymptomatic patients with incidentally detected HCV (IDHCV). Patients and Methods: Retrospective evaluation of liver biopsies was done in 113 patients with IDHCV, diagnosed during routine screening. Decision of liver biopsy was made on the basis of age, genotype, acceptable clinical, hematological, and biochemical profiles, and willingness of the patients to undergo treatment. Serum ALT levels, HCV RNA titers, and genotypes were correlated with HAI and F stage. Results: Genotyping was done in 77 of the 113 patients, of which genotype 3 was seen in 43 and genotype 1 in 25 patients. A higher fibrosis stage (Ishak's >F2) was noted in 23.8% of the biopsies. Serum ALT showed a significant correlation with the HAI score on liver biopsy (P = 0.01) but not with the stage of fibrosis (P = 0.52). HCV RNA titers did not reveal any correlation with HAI score or fibrosis stage. Conclusion: Serum transaminases and HCV RNA titers are poor predictors of disease severity and fibrosis. Since HCV shows a slow disease progression, higher stage may predict a worse prognosis irrespective of the low viral RNA load. Liver biopsy may help guide therapeutic decisions in IDHCV infection.